2011
DOI: 10.1007/s12598-011-0284-7
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation performance of methylene blue aqueous solution on Ag/g-C3N4 catalyst

Abstract: The graphitic carbon nitride (g-C 3 N 4 ) was synthesized by the polymerization of dicyandiamide, then silver hybrid g-C 3 N 4 (Ag/g-C 3 N 4 ) catalyst was prepared by photodeposition, deposition-precipitation, and doping methods. The first two methods deposited silver nanoparticles on the surface of g-C 3 N 4 semiconductor, while the last one embedded silver atom into the g-C 3 N 4 matrix without destroying the host structure. The photodegradation behavior of methylene blue (MB) aqueous solution over Ag/g-C 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
0
11
0
1
Order By: Relevance
“…Semiconductor photocatalysis is an effective and economic strategy to deal with the environmental problems caused by organic pollutants. Due to the unique electronic structure and physicochemical properties, g‐C 3 N 4 has been widely used for the photocatalytic degradation of various contaminants, including methyl orange (MO), rhodamine B (RhB), methylene blue (MB), aromatic compounds, aldehydes, and so on. The removal of inorganic toxic gas NO in air and the reduction of heavy metal ion Cr(VI) have also been investigated.…”
Section: Application Of G‐c3n4‐based Photocatalystsmentioning
confidence: 99%
“…Semiconductor photocatalysis is an effective and economic strategy to deal with the environmental problems caused by organic pollutants. Due to the unique electronic structure and physicochemical properties, g‐C 3 N 4 has been widely used for the photocatalytic degradation of various contaminants, including methyl orange (MO), rhodamine B (RhB), methylene blue (MB), aromatic compounds, aldehydes, and so on. The removal of inorganic toxic gas NO in air and the reduction of heavy metal ion Cr(VI) have also been investigated.…”
Section: Application Of G‐c3n4‐based Photocatalystsmentioning
confidence: 99%
“…Transition metals, such as Fe [20,21], Cu [22], Ta [23], Co [24], and Ag [25,26] were also deposited onto g-C 3 N 4 to form novel organic-inorganic composites, which strongly tuned the optical, electrical and chemical properties of g-C 3 N 4, and then dramatically enhanced the photocatalysis. Yan et al [27] reported that B-doped g-C 3 N 4 could enhance the photodegradation of rhodamine B under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…These shortcomings make it unable to stand alone in the eld of photocatalysis. For this reason, researchers have tried many methods to improve the photocatalytic activity of g-C 3 N 4 .Such as element doping [18,19], precious metal deposition [20,21], and semiconductor compounding [22,23]. At present, two-dimensional (2D) materials can be used in many places, including the eld of photocatalysis by their super large speci c surface area and suitable forbidden band width.…”
Section: Introductionmentioning
confidence: 99%